Modelling Multicast QoS Routing by using Best-Tree Search in And-or Graphs and Soft Constraint Logic Programming - Bistarelli, Stefano; Montanari, Ugo; Rossi, Francesca; Santini, Francesco (Electronic notes in theoretical computer science, 2007)
We suggest a formal model to represent and solve the multicast routing problem in multicast networks. To attain this, we model the network adapting it to a weighted and-or graph, where the weight on a connector corresponds to the cost of sending a packet on the network link modelled by that connector. Then, we use the Soft Constraint Logic Programming (SCLP) framework as a convenient declarative programming environment in which to specify related problems. In particular, we show how the semantics of an SCLP program computes the best tree in the corresponding and-or graph: this result can be adopted to find, from a given source node, the multicast distribution tree having minimum cost and reaching all the destination nodes of the multicast communication. The costs on the connectors can be described also as vectors (multi-dimensional costs), each component representing a different Quality of Service metric value. Therefore, the construction of the best tree may involve a set of criteria, all of which are to be optimized (multi-criteria problem), e.g. maximum global bandwidth and minimum delay that can be experienced on a single link.